PENYELESAIAN SENGKETA ANTARA PT. ASTRA CREDIT COMPANIES DENGAN KONSUMEN DALAM PERJANJIAN LEASING - Fahreza Surya Sumantri, Hendro Saptono*), Marjo (Diponegoro Law Journal, 2013)
Engagement is a term or expression which is abstract, which refers to the legal relationships in the field of wealth between two or more people or parties, where the legal relationship gave birth to one of the obligations of the parties involved in the legal relationship. Engagement born of the agreement is the most common in daily human life - today. This agreement will be undertaken where both parties have agreed or agreed to enter into this contract.The existence of the agreement as a source of engagement we can find its basis in Article 1233 Book of the Law - Civil Code which states that: "each - each engagement was born, as well as a good treaty law - law"Each activity must have a purpose therefore, the authors also have a purpose in this thesis, as for the purpose of this study was to determine the position of a third party to which ownership of the goods are still in the process included in the company's leasing companies and credit astra related legal dispute resolution process that is leasing the to 2 (two) to pawn items that are still in the process of leasing companies in corporate credit astra. The method used in this study is an empirical juridical approach, which means that in use to solve the problem in the first study to examine then proceed to conduct research on primary data in the field.From the research, how the settlement when disputes arise between the lease and the lessor can be done 5 ways: send a warning letter, deliberation, transferable (over credits), direct execution, and the courts. To avoid disputes between both parties that the lease and the lessor, then made a copy of the agreement is about the rights and obligations between the parties that must be fulfilled by each party. In this case the dispute or dispute settlement is made more effective by deliberation or peace than by way of settlement in court so that the parties should avoid settling disputes in court.